Juridical Review of Notary’s Liability for Storage and Force Majeure of Deed Minute in Notary Office - Julitha Ananda Putri; Thea Farina; Karlinae Bangas (Dinasti Research, 2024)
This research examines the responsibilities of Notaries regarding the storage and force majeure of the minutes of deeds at the Notary's office. Notaries are obliged to make and keep the minutes of deeds as part of the notary protocol according to the Notary Deed of Office. However, the lack of specific regulations regarding retention poses a risk of damage or loss of documents, especially in force majeure situations. Although the digital age offers alternatives to mitigate these risks, Indonesian positive law has yet to recognize digital storage as a legitimate solution. This research uses a normative legal approach to identify the relevant issues and concludes that clearer regulations are needed to protect the integrity and viability of notarial deeds in the future.